Endovascular management of a fractured dialysis catheter: a case report and review of retrieval techniques - Lin, Tianjun; Wang, Qiqi; Huang, Wei; Liu, Yang; He, Chunshui (Frontiers in Surgery, 2025)
BackgroundWith the advancements in endovascular techniques, reports of rare vascular complications have increased. This case describes the accidental fracture of a non-cuffed hemodialysis catheter and its subsequent endovascular management, offering valuable insights for the treatment of similar intravascular foreign bodies (IFBs).Case reportAn 83-year-old male with a non-cuffed catheter presented after a catheter fracture. Radiographic imaging confirmed migration of the fragment to the right atrium. After a multispecialistic collaboration assessment, endovascular retrieval was performed via right femoral access using a filter retrieval device under fluoroscopic guidance. The catheter fragment was successfully captured and removed without procedural complications. The patient recovered uneventfully and remained well at follow-up evaluations.ConclusionThis case highlights the efficacy and safety of percutaneous endovascular retrieval for managing IFBs, providing a minimally invasive alternative to surgery with high success rates. Meticulous catheter handling and regular integrity assessments are critical to prevent and promptly manage such events.